(untitled) (Sains Humanika, 2025)
Apprehensions have been raised about graduates’ employability. Data on unemployment and problems with work mismatch are rising. In fields unrelated to their studies, many graduates find employment. Considering this, structured interviews were used to perform a qualitative study. A series of questions were posed to ten informants. The inquiry is pertinent to the study’s goal. The study aims to: (i) determine the factors that the informant considered when selecting their field of study; (ii) determine whether the informant is willing to work in a field that differs from their studies; and (iii) determine the informant’s perspective on the matter of job mismatch. The study’s findings indicate that the age range of the informant is limited to those between the ages of 20 and 26. There are five informants of each gender, equally divided between females and men. Every informant is pursuing an undergraduate degree and has a bachelor’s degree. In general, the interest element played a large role in most respondents’ choice of study. Financial constraints led most informants to consent to labour in industries other than research. The informants concurred that job prospects ought to be viewed as future additions to experience, given the mismatch issue. In conclusion, the employability problem demonstrates that future graduates will not only be unable to select a career but will also require an increase in the added value of their talents to deal with the problem of job mismatch. While studying, skills can be developed as early as possible.